Enhancing coral growth on artificial reefs by electro deposition reef - Mohd., Adil (2012)
The global decline in reef health has prompted the need for effective reef management methodologies, including the development of active reef restoration measures. Major causes of coral reefs damage includeuncontrolled tourismand fishing activities. Electro Deposition Reef (EDR) is a technique to enhance coral growth on artificialreefs by using direct current. It hasdemonstrated to be a potential tool for the restoration of marine habitat. The development and installation of EDR test bed was done in2004 atPerhentian Island. The test bed consisting of Cluster A and Cluster B was located in front of the Marine Park Department Jetty. Cluster A includes the EDR setup, while Cluster B acts as control. Cluster A consists of a 10m x 5m x 1.5m PVC frame to support the EDR structure and 10 units of concrete reefs. While, Cluster B as a control test bed consist of 10 units of concrete reefs only. Concrete reefs deployed functions as medium for coral to grow. These dome shaped concrete reefs were developed by a marine contractor Dorken Reefs Resources. Coral and fish species at Cluster A and B were counted, recorded and compared. The fish and coral assemblage on the test bed were found to be abundant and diverse. The most abundant coral species was Acropora, and the most numerous fish was Razor Fish.The growth rate of Acroporarecorded showed the growth of88% faster than Control Cluster (B). The coral grew up to 75mm within 18 months compared to control cluster rateof 40 mm for 18 months.The abundance and diversity index of fish were calculated using Shannon Wiener Index and the results show that thefish distribution is more dominant in Cluster Aat 2.77, compared to Cluster B, at2.46.Installation of the solar panel requires the correct position to be achieved to obtain optimum output of voltage and current.Cloudy areas may not get enough sun exposure. Wet climates will corrode exposed parts more quickly and the cost of maintenance must be considered. From the results given,EDRtechnique contributes in enhancing coral growth and created more source of food for the marine habitats.